Latent Profiles of Physical Activity and Physical Competence in Relation to Perceived Classroom Peer Context in Primary School Students - Iiris Kolunsarka; Donna Niemistö; Sanna Ulmanen; Heidi Leppä; Kirsi Pyhältö (Journal of Physical Activity and Health, 2026)
Background : Schools play a central role in supporting children’s physical and social development. Physical competence, encompassing motor skills, fitness, and perceived ability, is a key determinant of engagement in active play and social interactions. Children vary in their levels and combinations of these competencies, which may influence their experiences of social well-being with peers. This study examined variation in physical competence and activity profiles among fifth-grade students and their associations with perceived classroom peer context. Methods : Participants were 392 Finnish fifth-grade students (149 girls and 183 boys; M age 11.19 [0.31] y). Physical competence was assessed using motor skill and fitness tests. Perceived competence and classroom peer context were evaluated using questionnaires. Latent profile analysis identified subgroups based on competence and device-measured physical activity. Associations between profiles and peer context were analyzed using the Bose–Chaudhuri–Hocquenghem approach. Results : Three profiles emerged: high (17%), moderate (45%), and low (38%). Students in the high profile demonstrated the highest physical performance, activity levels, and self-perceptions. Those in the low profile showed the weakest outcomes across indicators, with moderate-profile students between these groups. Profiles were associated with classroom peer context. Students in the high profile reported greater comfort, cooperation, and cohesion and lower conflict and isolation, whereas those in the low profile experienced less supportive peer environments. Conclusion : The findings highlight the interconnection between physical and social well-being. School-based initiatives that promote physical competence and activity should consider fostering peer dynamics to narrow gaps in physical competence and encourage lifelong engagement in physical activity.